Efeito da idade da mulher na dosagem sérica do FSH basal e na contagem dos folículos antrais Ovarianos - CASTRO, Eduardo Camelo de (2011)
OBJECTIVES: To establish the correlation between the curves of the AFC and serum basal FSH as well as to construct a nomogram correlating age with different values of antral follicles counts percentiles in infertile patients. METHODS: A cross-sectional study of patients treated at Fêmina Reprodução Humana was made from March 2010 to October 2011. The patients were submitted to transvaginal ultrasonography and basal FSH dosage from days 2 to 4 of their menstrual period. The patients included were the ones who were 21 to 45 years old, with regular menses, two healthy ovaries, without any evidence of endocrinopathies and that signed the consent. Patients excluded: smokers, with galactosemia or ovarian cysts, with antecedents of hepatopathies, ovarian surgeries or treated with chemotherapy or radiotherapy. Pearson s correlations coefficient was used to analyze the parametric data and Spearman`s test to the non parametric data. To evaluate the evolution of the AFC in relation to age of patients the percentiles 5th, 25th, 50th, 75th and 95th were used. A linear regression was made to understand the effect of age on the AFC. RESULTS: One hundred and seventy-two patients were included in the trial with a mean age of 32.7 years old. There was a weak correlation between the dose of basal FSH and the AFC (r = - 0,269). The age-related normogram for the 5rd, 25th, 50th, 75th and 95th percentile of antral follicle count revealed that changes were best fitted by a linear function. The percentiles that showed the highest correlations were 25 (r = - 0,960; p < 0,001), 50 (r = - 0,948; p < 0,001) and 75 (r = - 0,917; p < 0,001). All were statistically significant. CONCLUSIONS: The correlation between serum levels of FSH and AFC was negative and weak. A nomogram was constructed correlating age with different values of the percentiles of the antral follicle count in infertile women without endocrinopathies. There was a linear, strong and negative correlation in all percentiles.